Preparation method and application of MoS2 / Fe2O3-coated Fe-MOF modified carbon electrode

By using MoS2/Fe2O3@Fe-MOF to modify the carbon electrode in the bioelectric Fenton system, the problems of low cathode catalytic performance and complex electrode material preparation are solved, and efficient pollutant degradation and cost reduction are achieved.

CN119409314AActive Publication Date: 2025-02-11INNER MONGOLIA UNIVERSITY

Patent Information

Application Number
CN202510008048.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-11
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The cathode in the existing bioelectric Fenton system has low catalytic performance in the generation and activation of H2O2, poor performance in degrading pollutants, and the preparation of electrode materials is complex and costly.

Method used

Through the regulation of hydrothermal reaction solvent, the dissolved Fe is converted into Fe2O3 in the preparation of MOF, and the conductive properties are improved through the recombination of MoS2, the electron density of Fe2+/Fe3+ is regulated, and the electrofenton catalytic performance is increased.

Benefits of technology

The catalytic performance of the cathode on H2O2 is improved, the pollutant degradation ability is enhanced, the preparation process of electrode materials is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409314A_ABST
    Figure CN119409314A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a MoS2 / Fe2O3 (at) Fe-MOF modified carbon electrode, and the preparation method of the MoS2 / Fe2O3 (at) Fe-MOF modified carbon electrode comprises the following steps: preparation of Fe2O3 (at) Fe-MOF powder, preparation of isopropanol IPA-MoS2 nanosheet dispersion liquid, preparation of MoS2 / Fe2O3 (at) Fe-MOF composite material dispersion liquid, and preparation of the MoS2 / Fe2O3 (at) Fe-MOF modified carbon electrode. The problems that an existing cathode is low in HO generation and activation catalysis performance, the pollutant degradation performance is not ideal, electrode materials are complex to prepare, cost is high and the like are solved. The prepared composite electrode is applied to a BEF system, has high power density, good electron transport performance and excellent degradation performance on antibiotics, can be recycled for multiple times, and has a very wide application prospect in the field of electro-Fenton.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a preparation method and application of a MoS2 / Fe2O3@Fe-MOF modified carbon electrode. Background Art

[0002] With the development of society and the expansion of industrial scale, the types and discharge of wastewater are increasing, and a large number of highly toxic and difficult to degrade pollutants are emerging. Antibiotics, as the most widely used drugs, are widely used to prevent and treat diseases worldwide. Since antibiotics cannot be completely degraded in the digestive tract of humans and animals, they will enter the environment with excrement. The introduction of these exogenous compounds will not only cause continuous pollution to aquatic and terrestrial ecosystems, but also cause bacteria in nature to have drug resistance. The increase and spread of drug resistance of environmental pathogens will inevitably pose a threat to human public health. In order to ensure the ecological safety of the water environment, it is urgent to develop efficient wastewater treatment technology.

[0003] The bio-electro-Fenton (BEF) system is an emerging water treatment technology that combines Fenton technology, electrochemical technology and biotechnology. It has the advantages of mild operating conditions, low sludge production, high pollutant removal efficiency and low energy consumption, and has good application prospects in the field of wastewater treatment. In the bio-electro-Fenton system, the cathode often plays a vital role. It is related to the online generation of H2O2 by the two-electron reduction of oxygen and the decomposition of H2O2 to produce reactive oxygen species (ROS) to degrade organic pollutants. The cathode in the traditional bio-electro-Fenton system mainly includes iron and its oxide-loaded graphite, carbon felt, carbon fiber, carbon nanotubes, etc. The above materials have the advantages of good conductivity, corrosion resistance and low price, but the cathode has low H2O2 production; the activation efficiency of H2O2 is limited, and the degradation performance is not ideal. At present, the metal organic framework (Fe-MOF) material has a high specific surface area and a controllable pore structure, which can accelerate electron migration and Fe 2+ Regeneration, efficient generation and activation of H2O2, has become a very promising catalytic material in electro-Fenton catalysis, but polar solvents and high temperatures in the preparation of MOFs can lead to the dissolution of the central metal Fe and reduce the catalytic activity.

[0004] Therefore, constructing a low-cost cathode with dual catalytic properties of electrocatalysis and Fenton catalysis, good conductivity and excellent stability is a core issue that needs to be solved to improve the performance of the bio-electro-Fenton system in treating pollutants and promote its practical application. Summary of the invention

[0005] Based on this, the present invention provides a preparation method and application of MoS2 / Fe2O3@Fe-MOF modified carbon electrode, which converts dissolved Fe into Fe2O3 in the preparation of MOF by regulating the hydrothermal reaction solvent in one step, and regulates Fe 2+ / Fe 3+ The electron density of Fe2O3@Fe-MOF increases, thus increasing its electro-Fenton catalytic performance. The composite of MoS2 can improve the conductivity of Fe2O3@Fe-MOF and increase the electron transfer rate; 4+ / Mo 6+ The circulation of Fe 2+ / Fe 3+ The redox cycle strengthens the catalytic performance of electro-Fenton. It effectively solves the problems of low catalytic performance of the existing cathode for the generation and activation of H2O2, unsatisfactory performance in degrading pollutants, complex preparation of electrode materials, and high cost.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides a method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, comprising the following steps: S1: Add trivalent iron salt to deionized water, stir to dissolve, add ethanol and N,N-dimethylformamide DMF to mix, then add trimesic acid, stir to dissolve, add polyvinylpyrrolidone K30, stir at room temperature for 60 min, transfer to a reactor for hydrothermal reaction, cool naturally to room temperature after the reaction, centrifuge, wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder; S2: After natural molybdenite is ball-milled and sieved into powder, it is added into isopropyl alcohol (IPA) and subjected to ultrasonic exfoliation to obtain an isopropyl alcohol (IPA)-MoS2 nanosheet dispersion; S3: adding the Fe2O3@Fe-MOF powder obtained in S1 to the isopropyl alcohol IPA-MoS2 nanosheet dispersion obtained in S2, and ultrasonically mixing for 30-90 minutes to obtain a MoS2 / Fe2O3@Fe-MOF composite material dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with ethanol, add carbon black and perfluorosulfonic acid polymer Nafion D520, stir for 30-90 min, coat the surface of the carbon electrode, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode.

[0007] Preferably, in S1, the trivalent iron salt is FeCl3·6H2O or Fe(NO)3·9H2O.

[0008] Preferably, in S1, the concentration of the deionized water solution of the ferric salt is 75-100 mol / L, the volume ratio of the deionized water, ethanol and N,N-dimethylformamide is 1:1:1, the amount ratio of the ferric salt and trimesic acid is 1.5-2:1, and the concentration of the polyvinylpyrrolidone K30 in the solution is 20 g / L.

[0009] Preferably, in S1, the temperature of the hydrothermal reaction is 150-170° C., and the time is 3-12 h.

[0010] Preferably, in S2, the particle size of the natural molybdenum ore powder is ≤20µm, the solid-liquid ratio of the natural molybdenum ore powder and isopropyl alcohol IPA is 1:200, and the concentration of the isopropyl alcohol IPA-MoS2 nanosheet dispersion is 171 mg / L.

[0011] Preferably, in S2, the power of ultrasonic stripping is 350 W and the time is 24 h.

[0012] Preferably, in the S3, the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 0.5-2%.

[0013] Preferably, in S4, the volume ratio of the MoS2 / Fe2O3@Fe-MOF composite material dispersion to ethanol is 1:0.07-3.5; the mass ratio of carbon black to the MoS2 / Fe2O3@Fe-MOF composite material is 0.25-0.3:1; the mass ratio of the perfluorosulfonic acid polymer NafionD520 to the MoS2 / Fe2O3@Fe-MOF composite material is 1-1.3:1.

[0014] Preferably, in S4, the carbon electrode is a carbon plate, carbon felt or carbon cloth.

[0015] Based on the same inventive concept, the present invention also provides an application of a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the MoS2 / Fe2O3@Fe-MOF modified carbon electrode is used as the cathode of a bioelectric Fenton system to degrade antibiotics in wastewater.

[0016] The above one or more technical solutions of the present invention have the following technical effects: 1) The ratio of iron oxide and MOF in the MoS2 / Fe2O3@Fe-MOF modified carbon electrode is adjustable, and Fe2O3 and Fe-MOF synergistically regulate the adsorption and Fenton catalytic performance of the electrode material; 2) MoS2 is modified on the surface of MOF by ultrasonic mixing. No special instruments or complicated operation procedures are required. The amount of MoS2 catalyst can be easily controlled to avoid the aggregation of its sheets. The composite of MoS2 makes the electrode electrical properties better, accelerates electron transfer, and reduces the cathode overpotential. In addition, the doping of MoS2 can change the spin density distribution of the C electrode, which is beneficial to the two-electron reduction of O2. 3) The MoS2 two-dimensional nanosheets used as the catalyst in the present invention are derived from the direct stripping of molybdenite, which has low material cost, abundant sources, simple preparation process, strong controllability and low equipment requirements; 4) The composite electrode prepared by the present invention is applied to the BEF system, has high power density, good electron transmission performance, excellent degradation performance for antibiotics, and can be recycled for many times. It has a very broad application prospect in the field of electro-Fenton. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0018] Figure 1 , preparation process of MoS2 / Fe2O3@Fe-MOF modified carbon electrode; Figure 2 , XRD pattern of Fe2O3@Fe-MOF prepared in step S1 of Examples 1 to 4; Figure 3 , SEM image of MoS2 / Fe2O3@Fe-MOF prepared in Example 1; Figure 4 , TEM image of MoS2 / Fe2O3@Fe-MOF prepared in Example 1; Figure 5 , XRD pattern of MoS2 / Fe2O3@Fe-MOF prepared in Example 1; Figure 6 , power density curves of the materials prepared in Examples 1 to 6 and Comparative Examples 1 and 2; Figure 7 , CV graphs of the materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2; Figure 8 , EIS spectra of the materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2; Fig. 9 , Degradation curves of the materials prepared by Examples 1, 5, 6 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0020] Throughout the specification, unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a person skilled in the art to which the present invention belongs. If there is a conflict, the present specification takes precedence. The preparation process of MoS2 / Fe2O3@Fe-MOF modified carbon electrode is as follows Figure 1 shown.

[0021] Example 1 A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 1.5 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, and then add 1 mol trimesic acid. Stir to dissolve, then add 1.2 g polyvinyl pyrrolidone K30. After stirring at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160 °C for 3 h. After the reaction is completed, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder. S2: After natural molybdenite is ball-milled and sieved into a powder with a particle size of ≤20µm, 0.5g is taken and added into 100ml isopropanol IPA for ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain an isopropanol IPA-MoS2 nanosheet dispersion with a concentration of 171mg / L. S3: Add 0.055 g Fe2O3@Fe-MOF powder into 3.25 ml isopropanol IPA-MoS2 nanosheet dispersion and mix by ultrasonic for 30-90 min to obtain MoS2 / Fe2O3@Fe-MOF composite dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 and 3.75 ml of ethanol, add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 1%.

[0022] Example 2 A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 1.6 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, and then add 1 mol trimesic acid. Stir to dissolve, then add 1.2 g polyvinylpyrrolidone K30. After stirring at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160°C for 6 h. After the reaction is completed, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder. S2: After natural molybdenite is ball-milled and sieved into a powder with a particle size of ≤20µm, 0.5g is taken and added into 100ml isopropanol IPA for ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain an isopropanol IPA-MoS2 nanosheet dispersion with a concentration of 171mg / L. S3: Add 0.055 g Fe2O3@Fe-MOF powder into 3.25 ml isopropanol IPA-MoS2 nanosheet dispersion and mix by ultrasonic for 30-90 min to obtain MoS2 / Fe2O3@Fe-MOF composite dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with 3.75 ml of ethanol, add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 1%.

[0023] Example 3 A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 1.8 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, and then add 1 mol trimesic acid. Stir to dissolve, then add 1.2 g polyvinyl pyrrolidone K30. After stirring at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160 °C for 9 h. After the reaction is completed, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder. S2: After natural molybdenite is ball-milled and sieved into powder, 0.5 g is added to 100 ml isopropanol IPA and ultrasonically exfoliated at an ultrasonic power of 400 W for 24 h to obtain an isopropanol IPA-MoS2 nanosheet dispersion with a concentration of 171 mg / L. S3: Add 0.055 g Fe2O3@Fe-MOF powder into 3.25 ml isopropanol IPA-MoS2 nanosheet dispersion and mix by ultrasonic for 30-90 min to obtain MoS2 / Fe2O3@Fe-MOF composite dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with 3.75 ml of ethanol, add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 1%.

[0024] Example 4 A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 2 mol FeCl3·6H2O to 20 ml deionized water, stir and dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, mix, then add 1 mol trimesic acid, stir and dissolve, add 1.2 g polyvinyl pyrrolidone K30, stir at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160°C for 12 h, and cool to room temperature naturally after the reaction. Centrifuge and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder; S2: After natural molybdenite is ball-milled and sieved into powder, 0.5 g is added to 100 ml isopropanol IPA and ultrasonically exfoliated at an ultrasonic power of 400 W for 24 h to obtain an isopropanol IPA-MoS2 nanosheet dispersion with a concentration of 171 mg / L. S3: Add 0.055 g Fe2O3@Fe-MOF powder into 3.25 ml isopropanol IPA-MoS2 nanosheet dispersion and mix by ultrasonic for 30-90 min to obtain MoS2 / Fe2O3@Fe-MOF composite dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with 3.75 ml of ethanol, add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 1%.

[0025] Example 5 A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 1.5 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, and then add 1 mol trimesic acid. Stir to dissolve, then add 1.2 g polyvinyl pyrrolidone K30. After stirring at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160 °C for 3 h. After the reaction is completed, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder. S2: After natural molybdenite is ball-milled and sieved into a powder with a particle size of ≤20µm, 0.5g is taken and added into 100ml isopropanol IPA for ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain an isopropanol IPA-MoS2 nanosheet dispersion with a concentration of 171mg / L. S3: 0.055 g Fe2O3@Fe-MOF powder was added to 1.61 ml isopropanol IPA-MoS2 nanosheet dispersion and ultrasonically mixed for 30-90 minutes to obtain MoS2 / Fe2O3@Fe-MOF composite material dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with 5.39 ml of ethanol, add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 0.5%.

[0026] Example 6 A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 1.5 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, and then add 1 mol trimesic acid. Stir to dissolve, then add 1.2 g polyvinyl pyrrolidone K30. After stirring at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160 °C for 3 h. After the reaction is completed, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder. S2: After natural molybdenite is ball-milled and sieved into a powder with a particle size of ≤20µm, 0.5g is taken and added into 100ml isopropanol IPA for ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain an isopropanol IPA-MoS2 nanosheet dispersion with a concentration of 171mg / L. S3: Add 0.055 g Fe2O3@Fe-MOF powder into 6.55 ml isopropanol IPA-MoS2 nanosheet dispersion and mix by ultrasonic for 30-90 minutes to obtain MoS2 / Fe2O3@Fe-MOF composite material dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with 0.45 ml of ethanol, add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 2%.

[0027] Comparative Example 1 A method for preparing a Fe2O3@Fe-MOF modified carbon electrode comprises the following steps: S1: Add 1.5 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, add 20 ml ethanol and 20 ml N,N-dimethylformamide DMF, and then add 1 mol trimesic acid. Stir to dissolve, then add 20 ml polyvinylpyrrolidone K30. After stirring at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160°C for 3 h. After the reaction is completed, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder. S2: Add 0.055 g of Fe2O3@Fe-MOF powder to 7 ml of ethanol to fully disperse it, then add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry it at room temperature to obtain a Fe2O3@Fe-MOF modified carbon electrode.

[0028] Comparative Example 2 A method for preparing a MOF-modified carbon electrode comprises the following steps: S1: Add 1.5 mol FeCl3·6H2O to 20 ml deionized water, stir to dissolve, then add 1 mol H3BTC, stir at room temperature for 60 min, transfer to a reactor for hydrothermal reaction at 160°C for 12 h. After the reaction, cool naturally to room temperature, centrifuge, and wash and dry the separated solid to obtain Fe-MOF powder; S2: Add 0.055 g Fe-MOF powder to 7 ml ethanol to fully disperse it, then add 0.015 g carbon black and 50 μl perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry it at room temperature to obtain a Fe-MOF modified carbon electrode.

[0029] Test Example 1 The Fe2O3@Fe-MOF prepared in Examples 1-4 was subjected to X-ray diffraction (XRD) crystal structure analysis. The specific test results are as follows: Figure 2 As shown. Figure 2 It can be shown that the XRD pattern of the Fe2O3@Fe-MOF sample is consistent with the diffraction peak position and peak shape of hematite and MOF corresponding to the standard chart, proving that Fe2O3@Fe-MOF was successfully prepared. Figure 2 It can be seen from the intensity of each diffraction peak that with the increase of hydrothermal reaction time, the peak intensity of hematite diffraction peak becomes larger and the peak intensity of MOF diffraction peak becomes smaller. Therefore, the composition ratio of Fe2O3 / Fe-MOF composite materials can be controlled by adjusting the hydrothermal time according to different needs to achieve controllable preparation of the composite material composition.

[0030] Test Example 2 The MoS2 / Fe2O3@Fe-MOF prepared in Example 1 was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The specific test results are as follows Figure 3 , Figure 4 As shown. Figure 3 It can be seen that Fe2O3@Fe-MOF presents smooth spheres with uniform size and good dispersion. Figure 4It can be observed that MoS2 is in a flake state and is evenly distributed on the surface of the Fe2O3@Fe-MOF spheres, realizing the composite of the materials.

[0031] Test Example 3 The MoS2 / Fe2O3@Fe-MOF prepared in Example 1 was subjected to X-ray diffraction (XRD) crystal structure analysis. The specific test results are as follows: Figure 5 The XRD pattern of the sample is consistent with the diffraction peak positions and peak shapes of hematite, MOF, and MoS2 corresponding to the standard chart, proving that MoS2 is successfully composited with Fe2O3@Fe-MOF.

[0032] Test Example 4 The electrodes prepared in Examples 1-6 and Comparative Examples 1-2 were used as cathodes in a bio-electro-Fenton (BEF) system to measure the battery power density curve. The maximum power density of a battery can characterize the power generation performance of the battery, such as Figure 6 As shown in the figure, the power density of the battery with MoS2 / Fe2O3@Fe-MOF electrode as cathode (i.e., Examples 1 to 6) is higher than that of Comparative Example 1 (the maximum power density of Fe2O3@Fe-MOF electrode is 93.20 mW / m 2 ) and Comparative Example 2 (the maximum power density of the Fe-MOF electrode is 76.84 mW / m 2 ), and the hydrothermal reaction time and the MoS2 doping ratio in the composite electrode material affect the power density of the MoS2 / Fe2O3@Fe-MOF modified electrode. Among them, the power density of the battery using the MoS2 / Fe2O3@Fe-MOF modified carbon electrode of Example 1 (hydrothermal reaction time of 3h, MoS2 doping ratio of 1%) as the cathode is the highest (135.34 mW / m 2 ). This shows that deriving Fe-MOF into Fe2O3@Fe-MOF electrode material effectively improves the power generation performance of the battery, and doping MoS2 on its surface can further promote its electron transport ability.

[0033] The electrodes prepared in Example 1 and Comparative Examples 1-2 were subjected to cyclic voltammetry (CV) tests. Figure 7As shown, the cyclic voltammetry (CV) test results can analyze the difference in electrochemical activity between the MoS2 / Fe2O3@Fe-MOF modified carbon electrode of Example 1 (the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 1%) and Comparative Example 1 (Fe2O3@Fe-MOF electrode) and Comparative Example 2 (Fe-MOF electrode). The peak area and redox peak current of the CV curve are important indicators of the electrochemical activity of the electrode material. A larger peak area and a higher redox peak current usually mean that the material can transfer electrons more efficiently in the electrochemical reaction and provide more reaction sites. Compared with the Fe2O3@Fe-MOF electrode and the Fe-MOF electrode, the MoS2 / Fe2O3@Fe-MOF modified carbon electrode exhibits a larger peak area and a higher redox peak current, indicating that it has a stronger electrocatalytic performance.

[0034] The electrodes prepared in Example 1 and Comparative Examples 1-2 were subjected to electrochemical impedance spectroscopy (EIS) tests. Figure 8 As shown, the electrochemical properties of different electrode materials are analyzed by the semicircle diameter of the Nyquist curve. A smaller semicircle diameter indicates a lower charge transfer resistance, which means that the electron transfer during the electrochemical reaction is smoother and the reaction rate is faster. It can be seen that compared with Comparative Example 1 (Fe2O3@Fe-MOF electrode) and Comparative Example 2 (Fe-MOF electrode), the Nyquist curve semicircle diameter of the MoS2 / Fe2O3@Fe-MOF modified carbon electrode of Example 1 is the smallest, indicating that its charge transfer resistance is lower and the electron transfer rate is faster.

[0035] Test Example 5 The modified carbon electrodes prepared in Examples 1, 5, and 6 and Comparative Examples 1-2 were placed in the constructed dual-chamber BEF system as cathodes, and degradation experiments were carried out on 10 mg / L tetracycline (TC) simulated wastewater in the cathode chamber. The test results are shown in Figure 2. Fig. 9 shown.

[0036] The degradation rates of TC by the BEF system constructed by the 1% MoS2 / Fe2O3@Fe-MOF electrode of Example 1, the 0.5% MoS2 / Fe2O3@Fe-MOF electrode of Example 5, the 2% MoS2 / Fe2O3@Fe-MOF electrode of Example 6, the Fe2O3@Fe-MOF electrode of Comparative Example 1, and the Fe-MOF electrode of Comparative Example 2 were 99.47%, 91.26%, 94.56%, 88.96%, and 74.46%, respectively. It can be seen that the degradation effect of the BEF system of the MoS2 / Fe2O3@Fe-MOF modified carbon electrode on pollutants is significantly higher than that of the bio-electro-Fenton (BEF) system of the Fe2O3@Fe-MOF modified carbon electrode and the Fe-MOF modified carbon electrode, proving that the MoS2 / Fe2O3@Fe-MOF modified carbon electrode has a higher catalytic performance on the degradation of pollutants.

Claims

1. A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, characterized in that: The steps include: S1: Add trivalent iron salt to deionized water, stir to dissolve, add ethanol and N,N-dimethylformamide DMF to mix, then add trimesic acid, stir to dissolve, add polyvinylpyrrolidone K30, stir at room temperature for 60 min, transfer to a reactor for hydrothermal reaction, cool naturally to room temperature after the reaction, centrifuge, wash and dry the separated solid to obtain Fe2O3@Fe-MOF powder; S2: After natural molybdenite is ball-milled and sieved into powder, it is added into isopropyl alcohol (IPA) and subjected to ultrasonic exfoliation to obtain an isopropyl alcohol (IPA)-MoS2 nanosheet dispersion; S3: adding the Fe2O3@Fe-MOF powder obtained in S1 to the isopropyl alcohol IPA-MoS2 nanosheet dispersion obtained in S2, and ultrasonically mixing for 30-90 minutes to obtain a MoS2 / Fe2O3@Fe-MOF composite material dispersion; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with ethanol, add carbon black and perfluorosulfonic acid polymer Nafion D520, stir for 30-90 min, coat the surface of the carbon electrode, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode.

2. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S1, the trivalent iron salt is FeCl3·6H2O or Fe(NO)3·9H2O.

3. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S1, the concentration of the deionized water solution of the ferric salt is 75-100 mol / L, the volume ratio of the deionized water, ethanol, and N,N-dimethylformamide is 1:1:1, the amount ratio of the ferric salt to trimesic acid is 1.5-2:1, and the concentration of the polyvinylpyrrolidone K30 in the solution is 20 g / L.

4. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S1, the temperature of the hydrothermal reaction is 150-170°C and the time is 3-12 h.

5. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S2, the particle size of the natural molybdenum ore powder is ≤20µm, the solid-liquid ratio of the natural molybdenum ore powder and isopropyl alcohol IPA is 1:200, and the concentration of the isopropyl alcohol IPA-MoS2 nanosheet dispersion is 171 mg / L.

6. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S2, the power of ultrasonic peeling is 350 W and the time is 24 h.

7. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S3, the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 0.5-2%.

8. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S4, the volume ratio of the MoS2 / Fe2O3@Fe-MOF composite material dispersion to ethanol is 1:0.07-3.5; the mass ratio of carbon black to the MoS2 / Fe2O3@Fe-MOF composite material is 0.25-0.3:1; the mass ratio of the perfluorosulfonic acid polymer Nafion D520 to the MoS2 / Fe2O3@Fe-MOF composite material is 1-1.3:

1.

9. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S4, the carbon electrode is a carbon plate, carbon felt or carbon cloth.

10. An application of a MoS2 / Fe2O3@Fe-MOF modified carbon electrode prepared by the method according to any one of claims 1 to 9, characterized in that: The MoS2 / Fe2O3@Fe-MOF modified carbon electrode is used as the cathode of the bioelectric Fenton system to degrade antibiotics in sewage.

Citation Information

Patent Citations

  • Molybdenum sulfide / ferric oxide composite material and preparation method and application thereof

    CN106783201A

  • Method for efficiently removing organic wastewater through molybdenum disulfide catalysis assisted zero-valent iron heterogeneous electro-Fenton

    CN111217429A

  • Lithium ion battery negative electrode material with MOF derived core-shell structure and preparation method of lithium ion battery negative electrode material

    CN113451570A

  • Fe-pCOFs-MWCNTs / MoS2 nano composite material as well as preparation method and application thereof

    CN116814039A

  • Metal-organic framework electrodes for sodium ion batteries

    US20180053968A1

Cited By

  • Four-electrode electrochemical detection system and application thereof in pollutant detection

    CN120801456A